019 A Simple, Objective Estimate of Dietary Timing as a Circadian Biomarker. (3rd May 2021) - Hanlon, Erin; Nesheiwat, Wajdey; Sintetas, Stephanie; Van Cauter, Eve; Knutson, Kristen
Abstract: Introduction: The importance of diet for health has been recognized for centuries, yet, the focus has mostly been on what someone eats. Recently, however, focus has expanded to include when someone eats. Experimental studies that manipulated timing of food intake demonstrated effects on metabolic function. Most population-based studies have had to rely on self-reported methods to assess dietary behavior, including food logs or dietary recall, but self-report is subjective, error-prone, and burdensome. The goal of this analysis was to identify an objective estimate of dietary timing in clock time format. Further, we planned to examine whether sleep "chronotype" and this dietary "chronotype" are correlated. Methods: We used continuous glucose monitoring (CGM), which involves inserting a small sensor into the back of a participant's upper arm. It measures interstitial glucose levels every 5 minutes continuously for up to 2 weeks. We had 13 participants wear a CGM device for 2–10 days. We characterized dietary timing by simply identifying the clock time at which glucose levels were the highest. We identified this time point for each day and then calculated the mean clock time for each participant. Participants also wore wrist actigraphy for approximately one week and we calculated mean sleep start, sleep end, and midpoint times. We calculated intervals between highest glucose and sleep timing measures. Results: The mean time of highest glucose was 16:57 (SD 3:05) and ranged from 11:16 to 22:27. The mean (SD) intervals were 10.4 (2.9) hours for sleep end to highest glucose, 13.5 (2.8) hours for midpoint to highest glucose, and 5.8 (2.8) hours for highest glucose to sleep start. The correlations between highest glucose and sleep timing were .13 (p=.70) for sleep start, .05 (p=.88) for sleep end, and -.19 (p=.55) for midpoint. Conclusion: There was a wide range in the timing of highest glucose values in this sample, Further, the timing of highest glucose does not correlate with sleep timing, which indicates that these two timing measures are not redundant with one another. The timing of highest glucose from CGM may provide an objective, simple circadian biomarker of dietary behavior. Support (if any): P01A1011412-18A1